Osobennosti nejrodinamicheckogo reagirovanija borcov vysokoj kvalifikacii s raznym urovnem stressoustojchivosti - Korobeynikov, G.; Korobeynikova, L.; Mischenko, V. (Science in Olympic Sport, 2018)
Objective. To study the manifestation patterns of neurodynamic response at different levels of stress tolerance in elite wrestlers. Methods. The study involved 36 elite athletes aged 20-28 years, the members of Ukrainian national Greco-Roman wrestling team. To assess the level of stress tolerance, we used the "Stress test". To examine the neurodynamic response we studied the endurance of the nervous system, the speed of sensorimotor reactions, as well as the balance and mobility of nervous pro-cesses. All the techniques were part of the psycho-diagnostic complex «Multipsychometer-03". Results. The presence of a connection between the functional mobility of nervous processes and stress tolerance in elite wres-tlers predetermines the relationship between genetically determined factors of neurodynamic functions and the process of development of the psychological and emotional stability of an athlete in conditions of sporting activity. The obtained data demonstrated higher absolute values of the visual motor response time in wrestlers with a high level of stress tolerance that indicates a slowing of this response. Tolerance to stress does not affect the characteristics of speed visual response in the ath-letes. At the same time, the quality characteristics depend significantly on the ability to tolerate stress factors.In wrestlers with a high level of stress tolerance, there is a higher level of lability in the nervous system and the ability to re-produce a new motor action in conditions of development of cognitive skills. An increase in the threshold of stress tolerance contributes to optimization of the level of emotional stability of athletes due to the increased stress in the functional systems, as was clearly shown by the high rate of impulsiveness (premature response and increased inaccuracy) in executed actions. Conclusions. Manifestation of a high level of stress tolerance in elite wrestlers is associated with the emotional stability and is accompanied with the mobilization of appropriate psycho-physiological resources.